2020
DOI: 10.11646/phytotaxa.438.1.8
|View full text |Cite
|
Sign up to set email alerts
|

<p><strong>Lectotype of <em>Solidago</em> ×<em>niederederi </em>(Asteraceae) selected from a recently rediscovered original material</strong></p>

Abstract: Solidago ×niederederi Khek (1905: 22) is a hybrid between North-American S. canadensis Linnaeus (1753: 878) and European native S. virgaurea Linnaeus (1753: 880). Solidago canadensis was introduced to Europe in the 17th century (Kowarik 2003). It has spread invasively throughout Europe since the second half of the 19th century (Weber 1998), reaching, besides sites disturbed by human activity, also (semi)natural biotopes, as forest edges, abandoned meadows and field margins which are often inhabited by native S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Solidago canadensis L., commonly known as Canadian goldenrod, native to N. America is widely spread throughout Europe, Asia (China, Russia, Japan, and Taiwan), Australia and N. Zealand, where it is considered an aggressive invasive weed [ 2 , 3 , 4 ]. The taxon is highly diverse, prone to hybridization, and therefore characterized by extensive polyploidy [ 1 , 2 , 5 , 6 , 7 , 8 ]. It is known that two N. American invasive species, S. canadensis and S. gigantea Aiton, can hybridize with the European native S. virgaurea L. producing the hybrids S. × niederederi Khek (hybrid between S. canadensis and S. virgaurea ) and S. × snarskisii (hybrid between S. gigantea and S. virgaurea ) [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solidago canadensis L., commonly known as Canadian goldenrod, native to N. America is widely spread throughout Europe, Asia (China, Russia, Japan, and Taiwan), Australia and N. Zealand, where it is considered an aggressive invasive weed [ 2 , 3 , 4 ]. The taxon is highly diverse, prone to hybridization, and therefore characterized by extensive polyploidy [ 1 , 2 , 5 , 6 , 7 , 8 ]. It is known that two N. American invasive species, S. canadensis and S. gigantea Aiton, can hybridize with the European native S. virgaurea L. producing the hybrids S. × niederederi Khek (hybrid between S. canadensis and S. virgaurea ) and S. × snarskisii (hybrid between S. gigantea and S. virgaurea ) [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The taxon is highly diverse, prone to hybridization, and therefore characterized by extensive polyploidy [ 1 , 2 , 5 , 6 , 7 , 8 ]. It is known that two N. American invasive species, S. canadensis and S. gigantea Aiton, can hybridize with the European native S. virgaurea L. producing the hybrids S. × niederederi Khek (hybrid between S. canadensis and S. virgaurea ) and S. × snarskisii (hybrid between S. gigantea and S. virgaurea ) [ 5 , 6 , 7 , 8 , 9 ]. In 2004, S. canadensis , together with 17 other plant species was recorded as an invasive weed in Lithuania [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Available data confirm the occurrence of infraspecific cytotype variation in Solidago; however, taxa with a single ploidy level are more frequent than taxa with multiple cytotypes (Peirson et al 2012, Semple 2016. In Europe, two North American invasive species, S. canadensis Linnaeus (1753: 878) and S. gigantea Aiton (1789: 211) hybridize with native S. virgaurea Linnaeus (1753: 880) giving the hybrids: S. ×niederederi Khek (1905: 22), a hybrid between S. canadensis and S. virgaurea (Pliszko & Zalewska-Gałosz 2016, Skokanová et al 2020a, and S. ×snarskisii Gudžinskas & Žalneravičius (2016: 148), a hybrid between S. gigantea and S. virgaurea (Gudžinskas & Žalneravičius 2016). Both hybrids belong to Solidago sect.…”
Section: Introductionmentioning
confidence: 99%
“…Triplidago Gudžinskas and Žalneravičius (2016: 152) which is characterized by the formation of pseudorosettes on the apices of vegetative shoots (Gudžinskas & Žalneravičius 2016). Taxonomic treatment of S. ×niederederi and S. ×snarskisii was presented by Pliszko (2015), Skokanová et al (2020a), and Gudžinskas & Žalneravičius (2016), respectively. Solidago ×niederederi has been recorded in Austria, Italy, France, Germany, the United Kingdom, Denmark, Sweden, Norway, Finland, Czechia, Poland, Hungary, Slovakia, Romania, Lithuania, Latvia, and European part of Russia (Jaźwa et al 2018, Skokanová et al 2020b and references therein) whereas S. ×snarskisii has been evidenced only in Lithuania, Poland, European part of Russia, and Sweden, so far (Gudžinskas & Žalneravičius 2016, Pliszko 2018, Vinogradova & Galkina 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Solidago ×niederederi Khek (Asteraceae), a natural hybrid between the North American S. canadensis L. and the European S. virgaurea L. (Pliszko 2015;Pliszko and Zalewska-Gałosz 2016;Skokanová et al 2020a), has been reported from 17 countries in Europe, including Austria, France, the United Kingdom, Denmark, Sweden, Norway, Finland, Italy, Germany, Hungary, Romania, Czechia, Slovakia, Poland, Lithuania, Latvia, and Russia (Jaźwa et al 2018;Skokanová et al 2020b). It is considered as naturalized alien taxon in Austria, Poland, Lithuania and Latvia ( G u d ž i n sk a s a n d P e t ru l ai ti s 2 0 1 6; Pliszko and Kostrakiewicz-Gierałt 2017;).…”
Section: Introductionmentioning
confidence: 99%